2011 IEEE International Geoscience and Remote Sensing Symposium 2011
DOI: 10.1109/igarss.2011.6050092
|View full text |Cite
|
Sign up to set email alerts
|

Combining space-based and in-situ measurements to track flooding in Thailand

Abstract: We describe efforts to integrate in-situ sensing, space-borne sensing, hydrological modeling, active control of sensing, and automatic data product generation to enhance monitoring and management of flooding. In our approach, broad coverage sensors and missions such as MODIS, TRMM, and weather satellite information and in-situ weather and river gauging information are all inputs to track flooding via river basin and sub-basin hydrological models. While these inputs can provide significant information as to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 3 publications
(1 reference statement)
0
8
0
Order By: Relevance
“…The availability of sequences of flood extent provided by these methods are now allowing the validation of hydraulic models through a wider dynamic range of an event (Bates et al, 2006;Schumann et al, 2011), rather than just at a single point in the event, as well as being used in near real time to monitor floods (Chien et al, 2011;Auynirundronkool et al, 2012;McLaren et al, 2012). There are many potentially important flow processes active on a floodplain, such as floodplain channels and ditches providing flow connections (Nicholas and Mitchell, 2003) as well as barriers such as embankments, floodplain channel levees and woody debris blocking flow connections (Jeffiries et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The availability of sequences of flood extent provided by these methods are now allowing the validation of hydraulic models through a wider dynamic range of an event (Bates et al, 2006;Schumann et al, 2011), rather than just at a single point in the event, as well as being used in near real time to monitor floods (Chien et al, 2011;Auynirundronkool et al, 2012;McLaren et al, 2012). There are many potentially important flow processes active on a floodplain, such as floodplain channels and ditches providing flow connections (Nicholas and Mitchell, 2003) as well as barriers such as embankments, floodplain channel levees and woody debris blocking flow connections (Jeffiries et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…To train the team of rovers using the difference evaluation (in experiments that are completely independent from those in which the team is trained using the global evaluation), we directly apply Eqs. (1)(2)(3)(4), resulting in…”
Section: Rover Evaluation Functionsmentioning
confidence: 99%
“…It also provides new capabilities: temporally synchronized, but spatially separated measurements can be taken to measure ephemeral phenomena that simply could not be captured by a single monolithic rover [1]. Cooperating surface and orbital vehicles can even observe the same phenomena simultaneously [2]. Multiple rovers can cooperate on complex tasks, like construction, surpassing even the most capable single rover.…”
Section: Introductionmentioning
confidence: 99%
“…The solutions developed for single platforms are not necessarily transplantable in this distributed context. A number of studies have recently shown interest for the disaster management, focusing on sensorweb [1] or just on Earth Observation constellations [2], [3], [4], [5]. Most of them faced the problem with classic techniques such as greedy [5], [2], backtracking [3] or simple heuristics.…”
Section: Introductionmentioning
confidence: 99%